International validation of the EORTC QLQ‐CLL17 questionnaire for assessment of health‐related quality of life for patients with chronic lymphocytic leukaemia. (7th March 2022) - Oerlemans, Simone; Efficace, Fabio; Kieffer, Jacobien M.; Kyriakou, Charalampia; Xochelli, Aliki; Levedahl, Kerstin; Petranovic, Duska; Borges, Fabio Cardoso; Bredart, Anne; Shamieh, Omar; Gziskevicius, Laimonas; Lehmann, Jens; et al.
Summary: Selecting the most appropriate chronic lymphocytic leukaemia (CLL) treatment is challenging. Patient‐reported health‐related quality of life (HRQoL) is therefore a critical aspect to consider. This international study by the European Organization for Research and Treatment of Cancer (EORTC) tested the psychometric properties of a newly developed measure for CLL patients: the EORTC QLQ‐CLL17 to supplement the core questionnaire (EORTC QLQ‐C30). Patients with CLL ( n  = 341) from 12 countries completed the QLQ‐C30, QLQ‐CLL17 and a debriefing questionnaire. Sociodemographic and clinical data were recorded from medical records. A high percentage (30%–66%) reported symptoms and/or worries (e.g. aches/pains in muscles, lack of energy and worry/fears about health). Confirmatory factor analysis showed an acceptable to good fit of the 17 items on the three scales (i.e. symptom burden, physical condition/fatigue and worries/fears about health and functioning). Completion took on average 8 min. Test–retest and convergent validity was demonstrated. The QLQ‐CLL17 differentiated between patients with an Eastern Cooperative Oncology group (ECOG) performance of 0 versus 1–3 ( p 's < 0.01 and clinically relevant). The newly developed EORTC QLQ‐CLL17 will increase sensitivity of HRQoL assessment in patients with CLL. Implementation of this questionnaire both in clinical research and practice will help to generate unique clinically relevant data to better inform CLL treatment decision‐making.